2020
DOI: 10.1038/s41435-020-0105-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and significance of carbohydrate-specific antibodies

Abstract: Carbohydrate-specific antibodies are widespread among all classes of immunoglobulins. Despite their broad occurrence, little is known about their formation and biological significance. Carbohydrate-specific antibodies are often classified as natural antibodies under the assumption that they arise without prior exposure to exogenous antigens. On the other hand, various carbohydrate-specific antibodies, including antibodies to ABO blood group antigens, emerge after the contact of immune cells with the intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 235 publications
(266 reference statements)
1
67
0
Order By: Relevance
“…Hennet, 2020). Previous studies have demonstrated that autoimmune diseases, like Guillain-Barre syndrome, multiple sclerosis, and inflammatory bowel disease, are caused by carbohydrate-specific antibodies related to bacterial infection or gut microbes (Kappler and Hennet, 2020). A recent SARS-CoV-2 study showed that COVID-19 patients have unusually high IgM and IgG antibodies to self-carbohydrates, including gangliosides, N-linked glycans, LacNAc derivatives, blood group H1, and sialyl Lewis X (Butler and Gildersleeve, 2020), indicating the possibility of autoimmune disorders caused by these antibodies.…”
Section: Glycans and Autoimmunitymentioning
confidence: 99%
“…Hennet, 2020). Previous studies have demonstrated that autoimmune diseases, like Guillain-Barre syndrome, multiple sclerosis, and inflammatory bowel disease, are caused by carbohydrate-specific antibodies related to bacterial infection or gut microbes (Kappler and Hennet, 2020). A recent SARS-CoV-2 study showed that COVID-19 patients have unusually high IgM and IgG antibodies to self-carbohydrates, including gangliosides, N-linked glycans, LacNAc derivatives, blood group H1, and sialyl Lewis X (Butler and Gildersleeve, 2020), indicating the possibility of autoimmune disorders caused by these antibodies.…”
Section: Glycans and Autoimmunitymentioning
confidence: 99%
“…The subset of B cells absent from the fetal omentum are B2 cells. B2 and B1b cells are the predominant progenitors of immunoglobulin-producing plasma cells [ 218 ]. B1a cells are the main producers of the so-called natural antibodies, which, despite their microbiota-reactive specificity, can arise in the absence of exogenous microbiota and are represented mainly by antibodies of the IgM class, as well as IgA and IgG [ 219 ].…”
Section: Intestinal Immunoglobulinsmentioning
confidence: 99%
“…The function of natural antibodies is not known. By the eighth month of an infant’s life, the appearance of antibodies produced by B2 cells recognizing ABO and α-Gal antigens in addition to natural IgM indicates the maturation of specific antibodies to these antigens [ 218 ].…”
Section: Intestinal Immunoglobulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrates serve as a chief category of viral antigens which are easily identified by the host immune system that stimulates the production of Abs ( Katharina & Thierry, 2020 ). Thus, carbohydrates are called immunogen or antigen because they are able to induce as well to increase the immune response in the host.…”
Section: Carbohydrates-based Vaccine Strategiesmentioning
confidence: 99%